PENDAPATAN NASIONAL DAN KEGIATAN EKONOMI INDONESIA: ANALISIS PENGARUH DIGITALISASI TERHADAP PRODUK DOMESTIK BRUTO (PDB) PASCA-2025 - Rosdiana; Ignatius Septo Pramesworo; Sri Mulyono (Berajah Journal, 2026)
This study aims to analyse the impact of digitalisation on Indonesia’s Gross Domestic Product (GDP) post-2025 in the context of the transformation of the national economic structure. It employs a literature review using a qualitative-descriptive approach. The results indicate that digitalisation has become a key determinant of GDP growth, with the contribution of the digital economy rising from 7.7 per cent in the 2010–2014 period to 8.4 per cent in 2024, and projected to reach 9–10 per cent by 2026 and 15.5–19.6 per cent by 2045. This impact operates through three macroeconomic channels: an increase in total factor productivity on the production side; accelerated household consumption and investment in digital infrastructure on the expenditure side; and the diversification of digital service exports, which strengthens the resilience of the current account. However, the optimisation of the benefits of digitalisation remains hampered by regional infrastructure disparities, the risk of labour market disruption due to automation, and the concentration of market power in dominant platforms. In conclusion, digitalisation has fundamentally transformed Indonesia’s economic structure from a natural resource-based economy to a knowledge and technology-based economy, thereby requiring comprehensive policies that integrate the acceleration of broadband infrastructure, large-scale workforce reskilling programmes, and the strengthening of competition regulations to ensure inclusive and sustainable growth.